Are bipolar disorder, major depression, and suicidality linked with Toxoplasma gondii? A seromolecular case-control study. Issue 2 (17th February 2023) - Demirel, Ömer Faruk; Akgül, Özer; Bulu, Ersel; Tanrıöver Aydın, Ezgi; Uysal Cesur, Nuray; Aksoy Poyraz, Cana; Öner, Yaşar Ali
ABSTRACT: Objective: The existence of predisposing effects of latent Toxoplasma gondii ( T. gondii ) infection in bipolar disorder (BD), major depression (MD), and even suicide attempt (SA) has long been debatable. This conjecture remains unclear because there is a lack of evidence regarding how T. gondii manipulates the brain and behavior. Methods: We investigated the influence of T. gondii infection on BD and MD patients with or without SA compared to age-, sex-, and province-matched healthy controls (HCs) concurrently with serology and molecular-based evaluations. We prospectively assessed 147 volunteers with BD, 161 with MD, and 310 HCs. Results: T. gondii seropositivity rates were 57.1% for BD, 29.2% for MD, 64.8% for SA, and 21.3% for HC. Binary logistic regression analyses revealed that T. gondii positive Immunoglobulin G (IgG) status may be a prominent tendentious agent for BD (OR = 3.52; 95% CI [2.19–5.80]; p < 0.001) and SA (OR = 17.17; 95% CI [8.12–36.28]; p < 0.001), but not for MD (OR = 1.21; 95% CI [0.74–1.99]; p = 0.45). Nevertheless, the T. gondii DNA ratios determined by polymerase chain reaction (PCR) were linked to BD and MD. Conclusion: Our findings strongly support the burgeoning interest in the possibility that latent T. gondii infection may be relevant to the etiology of BD and SA, although this connection remains ambiguous.